CASE STUDY RESEARCH THROUGH A LOVE POEM - Tien, Le Hung (VNU Journal of Foreign Studies; Vol 35 No 5, 2019)
Case study is one of the common research methods in social sciences. However, at times this research method is still inappropriately interpreted and applied in language research in Vietnam. The article presents some general principles of case study research (Part I) and analyzes the application of these principles in a well-known love poem (Part II) with a hope to help researcher trainees have better understandings of the theory as well as the application of case study research method in applied linguistics.